The Precision Of The Giving Of The Drug Based On Service Identifikation Of Patien Compliance At “Darmayu” General Hospital Ponorogo - Ellina, Agusta Dian; Suwarno, Suwarno; Fawzi, Alfian (Universitas STRADA Indonesia, 2018)
The research was distributed by drug services granting conditions up to this moment there are still many problems. As for the problem of the research is